Factors Influencing Labor Absorption in the Micro and Small Industry Sector in Banten Province for the 2019-2023 Period - Vivin Hanitha; Hendra Hendra; Tri Angreni (eCo-Buss, 2025)
This research seeks to investigate how the quantity of industries, Gross Regional Domestic Product, Production Value, Minimum Wage affects Labor Absorption in the micro and small industry sector in Banten Province. With 8 regencies and cities in Banten and a research timeframe from 2019 to 2023 utilizing quantitative methods, the analysis employing multiple linear regression demonstrates that the model possesses exceptional explanatory power. The R-squared value of 0.989332 reveals that approximately 98.93% of the variation in the dependent variable (labor force number/Y) is accounted for by the independent variables. According to the findings of the regression analysis, the Gross Domestic Product (GDP) variable positively affects the level of employment (labor). This suggests that there is statistically inadequate evidence to claim that alterations in the number of industries, productivity levels, or minimum wage directly influence labor absorption levels. This condition could arise from factors beyond the primary model, or the third variable's influence may be of an indirect nature. This model indicates that GDP could be a key element affecting labor absorption, whereas other factors have not yet played a substantial role.